AUSTRALIAN SCHOLARSHIP ON INDONESIAN ISLAM: A Socio-historical Overview - Hilmy, Masdar; Zaini, Achmad; Syafaq, Hammis (JOURNAL OF INDONESIAN ISLAM, 2024)
This article analyzes the extent to which Australian scholarship portrays the reality of Indonesian Islam from a socio-historical perspective. This article argues that there is no such thing as interest-free in the process of knowledge production in Indonesian Islam studies. The production of knowledge on Indonesian Islam made by Australian scholars in Australian universities are inextricably linked to political and economic interests of the country. This article found out that academic production among Australian scholars is directed by the vision of the country in order to protect Australia and all Australian citizens both politically and economically. In addition, the academic production is designed to make a stable relationship between Indonesia and Australia. For Australia, the existence of Indonesia does matter as its major forefront in facing external threats such as military invasion, asylum seekers as well as immigrants. The stability of relationship will lead to the creation of economic prosperity among Australian citizens in general.